PENGARUH INTERVENSI TERHADAP PENGETAHUAN WARGA TENTANG DAGUSIBU DI PADUKUHAN KARANG TENGAH, SLEMAN - Margala Juang Bertorio; Rahmat A. Hi Wahid A Hi Wahid; Nurul Jannah; Anis Febri Nilansari; Hanifah Karimatulhajj (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The ease of access to information about drugs through online media is a challenge in disseminating correct drug information. One way to manage drugs that is good and right is to implement a DAGUSIBU counselling program (DApatkan, GUnakan, SImpan, BUang). The program initiated by the Indonesian Pharmacists Association is an effort to improve health for the community, which is carried out through health care activities by pharmacists. Community empowerment in Padukuhan Karang Tengah, Nogotirto, Gamping, Sleman, Yogyakarta supports increased understanding and knowledge of the community related to DAGUSIBU. This empowerment activity was used lecture and discussion methods. Before the activity, residents were given a pretest to find out the level of knowledge. Than, posttest was given to all respondent to find out the change knowledge. The results of the pretest show that 66.67% of the correspondent is in a very knowledgeable group. After the intervention, as much as 89.22% of the people were in the group of very know. Interventions in the community increased community knowledge about DAGUSIBU by 22.59%. Other research is needed with a longer duration of the intervention and the distance between pretest and posttest for one month.